The Effect of Plant Extracts on In-vitro Ruminal Fermentation, Methanogenesis and Methane-related Microbes in the Rumen - Kim, E. T. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The effect on methanogens attached to the surface of rumen ciliate protozoa by the addition of plant extracts (pine needles and ginkgo leaves) was studied with particular reference to their effectiveness for decreasing methane emission. The plant extracts (pine needles and ginkgo leaves) were added to an in vitro fermentation incubated with rumen fluid. The microbial population including bacteria, ciliated-associated methanogen, four different groups of methanogens and Fibrobacter succinogenes were quantified by using the real-time PCR. Gas profiles including methane, carbon dioxide and hydrogen, and runinal fermentation characteristics were observed in vitro. The methane emission from samples with an addition of individual juices from pine needles, ginkgo leaves and 70% ethanol extract from ginko leaves was significantly lower (p<0.05, 27.1, 28.1 and 28.1 vs 34.0 ml/g DM) than that of the control, respectively. Total VFAs in samples with an addition of any of the plant extracts were significantly lower than that of the control (p<0.05) as well. The order Methanococcales and the order Methanosarcinales were not detected by using PCR in any incubated mixtures. The ciliate-associated methanogens population decreased from 25% to 49% in the plant extacts as compared to control. We speculate that the supplementation of juice from pine needles and ginkgo leaves extract (70% ethanol extract) decreased the protozoa population resulting in a reduction of methane emission in the rumen and thus inhibiting methanogenesis. The order Methanobacteriales community was affected by addition of all plant extracts and decreased to less than the control, while the order Methanomicrobiales population showed an increase to more than that of the control. The F. succinogenes, the major fibrolytic microorganism, population in all added plant extracts was increased to greater than that of the control. In conclusion, pine needles and ginkgo leaves extracts appear to have properties that decrease methanogenesis by inhibiting protozoa species and may have a potential for use as additives for ruminants.